Mutual Coupling reduction in Dual-Band MIMO Antenna using Parasitic Dollar-Shaped Structure for Modern Wireless Communication - Sim, Chow-Yen-Desmond; Dhasarathan, Vigneswaran; Tran, Thien Khanh; Kulkarni, Jayshri; Garner, Brian; Li, Yang (IEEE access, 2023)
A dual-band Multiple Input Multiple Output (MIMO) antenna with low mutual coupling is analyzed and studied for Fifth Generation (5G) sub 6 GHz and Wireless Fidelity (Wi-Fi) 6E frequency-band applications. Each of the identical monopole radiators consists of a rectangular patch, inverted-E, and asymmetrical T-shaped strip to generate 5G sub 6 GHz and Wi-Fi 6E frequency bands. The deployment of the radiators horizontally with end-to-end separation of 5mm makes the antenna compact with an overall dimension of 45×30mm 2 (0.37λ×0.25λ for λ at the lower resonating frequency of 2.5GHz). The antenna achieves measured impedance bandwidths of 2.39 to 2.57 GHz, and of 3.82 to 6.95 GHz, at two resonating frequencies of 2.5 GHz and 4.5 GHz, respectively. A Parasitic Dollar Shaped Structure (PDSS) introduced between the two monopole radiators to suppress the surface waves of each monopole reduces the measured mutual coupling up to -15dB throughout the operating band. Furthermore, the measured gain, radiation efficiency, Envelope Correlation Coefficient (ECC), and Diversity Gain (DG) values remain in good agreement with simulated values and are well above the minimum limit set by industry standards. These results affirm the applicability of the MIMO antenna for 5G and Wi-Fi 6E frequency bands.